Integrated Transcriptome and Metabolome Analysis Revealed the Molecular Mechanism of Anthocyanin Synthesis in Purple Leaf Pepper (Capsicum annuum L.) under Different Light Intensities - Yiyu Shen; Lianzhen Mao; Yao Zhou; Ying Sun; Zhoubin Liu; Chengliang Liang (Horticulturae, 2023)
Light is a crucial environmental component for plant growth, and light intensity plays a crucial function in controlling pigment anabolism in plants. We performed physiological characterisation, transcriptome, and metabolome investigations on purple leaf peppers treated with different light intensities to evaluate the effect on plant leaf colour. The results showed that the leaves of the peppers became significantly purplish under high light, with significantly higher anthocyanin, chlorophyll a, and carotenoid contents. A total of 44,263 genes were quantified using RNA-Seq, with the photoprotein-related genes LRP and LIP maintaining high expression levels under high and medium light. The anthocyanin synthesis pathway was variously enriched among the comparison groups, according to KEGG. The expression of the genes involved in the anthocyanin synthesis pathway, such as CHI, F3H, DFR, and BZ1, was significantly higher under high light. In addition, MYB and bHLH gene families were the most abundant, and MYB1R1, MYB113-like, and bHLH90-like were significantly expressed under high light and highly positively correlated with the above anthocyanin synthesis genes. According to our metabolomic analysis, delphinidin-3-O-rutinoside and delphinidin-3-O-glucoside accumulated in significant concentrations in purple leaves under high light. This study is useful for understanding the process of anthocyanin synthesis and metabolism in pepper leaves that is generated and regulated by varied light intensity.